A rapid and efficient method for DNA extraction from paraffin wax embedded tissue for PCR amplification. Issue 3 (June 1996) - Morgan, Kevin; Lam, Letty; Kalsheker, Noor
Abstract : DNA from archival, formaldehyde fixed, paraffin wax embedded human tissue, suitable for amplification by the polymerase chain reaction (PCR), was obtained using a microwave method based on the capture of DNA by magnetic beads. Fragments of the α-1-antitrypsin gene (AAT) and the apolipoprotein E gene (APOE) were amplified successfully from human liver and brain tissue, respectively. This procedure provides a more rapid, simple and efficient method for reproducibly obtaining DNA from preserved tissue that has been kept in storage for up to 30 years.